Exploring Iranian EFL Learners’ Attitudes towards English Language Norms and Their Impacts on Ideal L2 Self, Criterion Measure, Cultural Interest, and Integrativenes - Lsskari Kalat, Fatemeh; Ghanizadeh, Afsaneh (Journal of English Language and Literature (ISSN: 2368-2132), 2017)
This study investigated the Iranian EFL learners’ attitudes toward English norms (standard vs. nativized). Moreover, the roles played by these attitudes in some motivational factors were examined. The study utilized a mixed-methods approach (QUAN→qual). To this end, four participants were interviewed for the QUAL part and 162 EFL learners were selected for QUAN phase from different private language institutes and universities in Mashhad and Nyshaboor, two cites in northeast of Iran. They were asked to complete a battery of two questionnaires: 1) Attitudes towards English language norms in the expanding circle questionnaire (Khatib & Rahimi, 2015) and 2) Dornyei’s L2 motivational self-system questionnaire. The results of structural equation modeling (SEM) indicated that attitudes to English language norms positively and significantly predicted all the motivational components: Ideal L2 self (β= .32, t= 4.09), criterion measure (β= .29, t= 3.85), cultural interest (β= .33, t= 5.12), and integrativenes (β= .28, t= 3.33). The results of interviews were in line with those of quantitative phase. The conclusions and pedagogical implications of the investigation as well as limitations and suggestions for further research were discussed.